2018
DOI: 10.3389/fnmol.2018.00178
|View full text |Cite
|
Sign up to set email alerts
|

Stable STIM1 Knockdown in Self-Renewing Human Neural Precursors Promotes Premature Neural Differentiation

Abstract: Ca2+ signaling plays a significant role in the development of the vertebrate nervous system where it regulates neurite growth as well as synapse and neurotransmitter specification. Elucidating the role of Ca2+ signaling in mammalian neuronal development has been largely restricted to either small animal models or primary cultures. Here we derived human neural precursor cells (NPCs) from human embryonic stem cells to understand the functional significance of a less understood arm of calcium signaling, Store-ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 143 publications
(164 reference statements)
2
33
1
Order By: Relevance
“…SOCE is one of these processes and is triggered by G-protein coupled PLC activation, a signalling mechanism used by several cell surface receptors that are expressed in the human cerebral cortex and reported to be important for brain function [e.g metabotropic glutamate receptor] and PLC signalling has also been linked to several brain disorders 29 . Studies in murine neural precursor cells (NPCs) have shown robust SOCE and depletion of STIM1 or ORAI1, key elements of SOCE results in defective NPC proliferation 30 ; a recent study has also suggested a conserved role for SOCE in human NPC proliferation 31 . In this study we developed protocols to monitor SOCE during in vitro differentiation and found a dynamic pattern of SOCE activity.…”
Section: Discussionmentioning
confidence: 99%
“…SOCE is one of these processes and is triggered by G-protein coupled PLC activation, a signalling mechanism used by several cell surface receptors that are expressed in the human cerebral cortex and reported to be important for brain function [e.g metabotropic glutamate receptor] and PLC signalling has also been linked to several brain disorders 29 . Studies in murine neural precursor cells (NPCs) have shown robust SOCE and depletion of STIM1 or ORAI1, key elements of SOCE results in defective NPC proliferation 30 ; a recent study has also suggested a conserved role for SOCE in human NPC proliferation 31 . In this study we developed protocols to monitor SOCE during in vitro differentiation and found a dynamic pattern of SOCE activity.…”
Section: Discussionmentioning
confidence: 99%
“…Both the suppression and deletion of STIM1 or Orai1 significantly alleviate the proliferation of embryonic and adult NPCs [53]. STIM1 knockdown also decreases the proliferation and early differentiation of human NPCs [54]. In addition to Orai activation, STIM proteins may induce Ca 2+ influx via TRPCs [5,55].…”
Section: Stim Proteins Under Physiological Conditionsmentioning
confidence: 99%
“…Furthermore, STIM1 protein is responsible for mGluR1-dependent synaptic transmission in cerebellar Purkinje neurons (Hartmann et al, 2014 ). Accumulating evidence indicates a role for STIM1 in neurogenesis (Somasundaram et al, 2014 ) and the proliferation and early differentiation of neural progenitor cells (NPCs) (Somasundaram et al, 2014 ; Gopurappilly et al, 2018 ). The knockdown of both STIM isoforms reduced SOCE and inhibited the entry of mouse embryonic stem cells into a neural lineage (Hao et al, 2014 ).…”
Section: Neuronal Ca 2+ Signaling Via Store-operatmentioning
confidence: 99%